TRANSGENERATIONAL TRAUMA, RESILIENCE, AND THE MEANING OF LIFE AMONG PALESTINIAN REFUGEE WOMEN: A NARRATIVE ANALYSIS OF HOPE AND PAIN - Owies, Rasha (An-Najah National University, 2025)
This study examined intergenerational trauma, psychological resilience, and meaning of life among four generations of Palestinian refugee women at Jenin camp. Jenin camp hosts refugee women from the Nakba of 1948 and the West Bank, and the camp women acquired a sample of 25 women of disparate age cohorts (15-80). The women were recruited via snowball sampling. The study aimed to document the cycles of trauma and the subsequent socio-psychological ramifications on Palestinian women Jenin camp, alongside the socio-psychological consequences from the trauma of insecurity, daily struggles, and intermittent hostilities. This research traced the intergenerational socio-psychological impacts of the Nakba and the trauma socio-psychological effects on four generations of Palestinian refugee women. The data demonstrated that even with the decreasing quality of life and the pain of losing one’s country and family, living in brutal conditions amidst the continuous occupation, refugee women possess high levels of psychological fortitude that is established in a complex concept of hope. Great hope is the hope of return, while small hope is the hope for a life with dignity and stability. Consequently, the data suggest that psychosocial support programs should meet the needs of refugee women to maintain their hope, strengthen their psychosocial support, and help them in working towards their collective dreams such as return.
الصدمة عبر الأجيال ، والمرونة ، ومعنى الحياة بين اللاجئات الفلسطينيات: تحليل سردي للأمل والألم